2018
DOI: 10.4142/jvs.2018.19.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Coactosin-like protein 1 inhibits neuronal migration during mouse corticogenesis

Abstract: Coactosin-like protein 1 (Cotl1), a member of the actin-depolymerizing factor (ADF)/cofilin family, was first purified from a soluble fraction of Dictyostelium discoideum cells. Neuronal migration requires cytoskeletal remodeling and actin regulation. Although Cotl1 strongly binds to F-actin, the role of Cotl1 in neuronal migration remains undescribed. In this study, we revealed that Cotl1 overexpression impaired migration of both early- and late-born neurons during mouse corticogenesis. Moreover, Cotl1 overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 34 , 35 Therefore, none of these proteins appear functionally relevant with the cardiac fibrotic phenotype. Interestingly, COTL1 was reported to be involved in TGF-β signaling 36 and inhibit neuronal migration during mouse corticogenesis, 37 suggesting that COTL1 could be a Cfast binding protein to regulate cardiac fibrosis. To confirm the mass spectrometry data, we performed a Cfast RNA pull-down assay coupled with western blotting to detect COTL1 after the lncRNA Cfast pull-down.…”
Section: Resultsmentioning
confidence: 99%
“… 34 , 35 Therefore, none of these proteins appear functionally relevant with the cardiac fibrotic phenotype. Interestingly, COTL1 was reported to be involved in TGF-β signaling 36 and inhibit neuronal migration during mouse corticogenesis, 37 suggesting that COTL1 could be a Cfast binding protein to regulate cardiac fibrosis. To confirm the mass spectrometry data, we performed a Cfast RNA pull-down assay coupled with western blotting to detect COTL1 after the lncRNA Cfast pull-down.…”
Section: Resultsmentioning
confidence: 99%
“…Early- and late-born cortical neurons display distinct migratory behaviors 63 . A study conducted by Li et al revealed that COTL1 overexpression impaired migration of both early- and late-born neurons during mouse corticogenesis, which suggests COTL1 was required for both somal translocation and locomotion, which can further impact cognitive/emotional/behavioral development 64 . Additionally, a study conducted by Bosch et al shows that miR-30b was downregulated in the VTA of methamphetamine self-administering rats 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this new PCV species was designated PCV3 [22]. The virus has since been identified in multiple countries, including Germany [24], Japan [25], Korea [26], Russia [27], China [28], Thailand [29], Italy [30], Spain [31], Denmark [32], South Korea [33], Poland [34], Brazil [35], and Sweden [36]. While testing is somewhat limited to date, the finding of PCV3 in retrospective samples indicates that this species of circovirus has likely been circulating in swine populations decades prior to the initial detection and case reports [36].…”
Section: Introductionmentioning
confidence: 99%